Disease Control Priorities, Third Edition : Volume 3. Cancer - Gelband, Hellen; Jha, Prabhat; Sankaranarayanan, Rengaswamy; Horton, Susan (Washington, DC: World Bank, 2015)
From its inception, the Disease Control Priorities series has focused attention on delivering efficacious health interventions that can result in dramatic reductions in mortality and disability at relatively modest cost. The approach has been multidisciplinary, and the recommendations have been evidence-based, scalable, and adaptable in multiple settings. Better and more equitable health care is the shared responsibility of governments and international agencies, public and private sectors, and societies and individuals, and all of these partners have been involved in the development of the series.